2021
DOI: 10.3934/jimo.2020115
|View full text |Cite
|
Sign up to set email alerts
|

Tabu search guided by reinforcement learning for the max-mean dispersion problem

Abstract: We present an effective hybrid metaheuristic of integrating reinforcement learning with a tabu-search (RLTS) algorithm for solving the maxmean dispersion problem. The innovative element is to design using a knowledge strategy from the Q-learning mechanism to locate promising regions when the tabu search is stuck in a local optimum. Computational experiments on extensive benchmarks show that the RLTS performs much better than stateof-the-art algorithms in the literature. From a total of 100 benchmark instances,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This is done by assigning rewards to the parameter change in the algorithm, storing them in a matrix, and learning the best values to apply to each parameter at runtime. In [47], another combination of a metaheuristic algorithm with reinforcement learning techniques is proposed. In this case, the tabu search was integrated with Q-Learning to find promising regions in the search space when the algorithm is stuck in a local optimum.…”
Section: Related Workmentioning
confidence: 99%
“…This is done by assigning rewards to the parameter change in the algorithm, storing them in a matrix, and learning the best values to apply to each parameter at runtime. In [47], another combination of a metaheuristic algorithm with reinforcement learning techniques is proposed. In this case, the tabu search was integrated with Q-Learning to find promising regions in the search space when the algorithm is stuck in a local optimum.…”
Section: Related Workmentioning
confidence: 99%
“…This integration has led to significant advancements across several research domains. Innovations in local search optimization [32], dynamic parameter tuning [33], and the identification of promising search areas represent key areas of progress [34]. Studies have demonstrated the efficacy of this integration in enhancing algorithmic intelligence and adaptability, contributing to fields ranging from optimization challenges in theoretical contexts to practical applications like neural network training and cloud computing load balancing [35,36].…”
Section: Related Workmentioning
confidence: 99%
“…It is carried out by assigning rewards to the change of parameters in the algorithm, storing them in an array, and learning the best values to apply to each parameter at runtime. In [46], another combination of a metaheuristic algorithm with reinforcement learning techniques is proposed. In this case, tabu search was integrated with Q-Learning to find promising regions in the search space when the algorithm is stuck at a local optimum.…”
Section: Related Workmentioning
confidence: 99%